Ethnobotany of the Kiluhikturmiut Inuinnait of Kugluktuk, Nunavut, Canada - Davis, Jonathan Duffy; Banack, Sandra Anne (Ethnobiology Letters, 2012)
The disparity in floral diversity between tropical and arctic regions is reflected in a paucity of ethnobotanical research among arctic cultures. The Kiluhikturmiut Inuinnait are an Inuit subpopulation who inhabit the Kitikmeot Region of the Territory of Nunavut in Canada’s Arctic. We conducted an ethnobotanical survey in the Inuinnait hamlet of Kugluktuk to document the traditional uses of plants as food, materials, and medicine. Data were gathered through unstructured interviews, participant observation, purposive sampling, and voucher-specimen collection of all plants used. Uses were documented for 23 plant species/types contained in 14 families. Nine species/types were eaten, six species/types were used as materials, and 12 species were used for medicine. Villagers shared common knowledge of plants used for food and materials; however, knowledge of medicinal plants was restricted to a single healer. We argue that specialized knowledge such as the use of medicinal plants is important to document especially when the number individuals using this knowledge is dwindling.